PELAJARAN PENTING DALAM MASA PEMERINTAHAN ORDE BARU - Leonard Tasuno Laiya (Jurnal Hukum Adigama, 2021)
Dur ng the New Order era  he  (often  abbrev ated  as  New  Order)  was  the  term  for  the  re gn  of  Pres dent  Soeharto   n   ndones a.  The  New  Order  was  founded  by  the  Old  Order,  wh ch  refers  to  the  era  of  Soekarno's  government.  As  we  know,  th s  new  order  era  occurred  after  the  destruct on  of  the  old  order  and  before  the  format on  of  the  reform  order  unt l  now  The  b rth  of  the  New  Order  began  w th  the   ssuance  of  an  Order  on  March  11,  1966.  The  New  Order  lasted  from  1966  to  1998.  At  that  t me  he  appo nted  Sukarno  as  the  f rst  Pres dent  of  the  Republ c  of   ndones a.  The  transfer  of  off ce  occurred   n  1966,  w th  the  replacement  of  the  old  order  wh ch  referred  to  the  era  of  Pres dent  Soekarno's  adm n strat on.  Wh ch  has  stepped  down  s nce  the  G30S  PK    nc dent  emerged.   n  th s  art cle,  we  w ll  d scuss  the  h story  of  the  old  order  from  the  beg nn ng  of   ts  format on  to  the  format on  of  the  next  per od,  namely  the  new  order.   n  th s  art cle  we  w ll  also  d scuss  the  h story  of  the  new  order  and  other   mportant  events,  and  w ll  also  d scuss  the  h story  of  the  reformat on  era,  namely  the  per od  when  the  new  order  was  destroyed  and  replaced  by  a  new  per od,  namely  the  reform  era  that  has  been   n  effect  unt l  now